Enhancing intercultural communicative competence in EFL classrooms: Strategies and techniques in Indonesian high schools - Fardini Sabilah; Bayu Hendro Wicaksono; Thathit Manon Andini (Research and Development in Education (RaDEn), 2025)
In the era of global communication, English as a Foreign Language (EFL) teachers are increasingly encouraged to integrate intercultural communication competence (ICC) into their language classes. This study explores how teachers' strategies and techniques enhance ICC in EFL classrooms at an Islamic secondary school in Malang. A qualitative case study design was used to gather in-depth data through semi-structured interviews, classroom observations, and documentation. The study found that strategies such as discussion, role-play, text analysis, and cultural reflection contributed to improving students' ICC. However, the study also highlights the need for more experiential learning approaches, such as simulations and cross-cultural collaborative projects, to provide deeper and more authentic intercultural experiences.